Valeurs et normes sociales dans le projet d'émancipation de Cornelius Castoriadis - Christophe Premat (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2019)
The purpose of this article is to analyze the philosophy of values developed by Cornelius Castoriadis from his theory of the imaginary institution of societies. By understanding the emergence of imaginary significations, it is possible to identify their manifestations through the representations, the affects and the intentions of individuals. In this context, values correspond to a series of significations that motivate the conduct of individuals. In fact, in a specific society, individuals believe in symbols that make sense for them. The presentation of the values does not reflect a moral project, but rather a socio-political construction that must be carefully described in order to identify the alteration of values over time. The article explores the way in which Castoriadis poses the problem of the persistence of past values with the risk of depending on established norms without being able to really transform them. In this perspective, Castoriadis refers to a fundamental value which is that of autonomy capable of questioning existing imaginaries.